1999
DOI: 10.1016/s0014-5793(99)01413-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro endosome‐lysosome transfer of dephosphorylated EGF receptor and Shc in rat liver

Abstract: We have studied the endosome-lysosome transfer of internalized epidermal growth factor receptor (EGFR) complexes in a cell-free system from rat liver. Analytical subfractionation of a postmitochondrial supernatant fraction showed that a pulse of internalized 125 I]EGF to the cytosol was detected. To assess the fate of the internalized EGFR protein over the time course of the endo-lysosomal transfer of the ligand, the effect of a saturating dose of native EGF on subsequent lysosomal targeting of the EGFR was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…SCF induces the phosphorylation and monoubiquitination of c-KIT, which are necessary for Grb2 association and endocytosis, respectively. The dephosphorylation of internalized RTKs occurs on early endosomes (7,35). We observed that the kinetics of c-KIT in the early phases, such as phosphorylation, dephosphorylation, endocytosis from the cell surface, and exit from early endosomes, were not affected by the loss of SMAP1.…”
Section: Figurementioning
confidence: 76%
“…SCF induces the phosphorylation and monoubiquitination of c-KIT, which are necessary for Grb2 association and endocytosis, respectively. The dephosphorylation of internalized RTKs occurs on early endosomes (7,35). We observed that the kinetics of c-KIT in the early phases, such as phosphorylation, dephosphorylation, endocytosis from the cell surface, and exit from early endosomes, were not affected by the loss of SMAP1.…”
Section: Figurementioning
confidence: 76%
“…Recently, Authier & Chauvet (1999) demonstrated that Shc is associated with the endocytosed EGFR. In addition, c-Src is reported to be enriched in the endosomal membranes in a ®broblast cell line that is derived from Rat-1 cells (Kaplan et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, receptor retention in the endosomes may trigger an alternate signal transduction cascade that leads to inhibition rather than activation of DNA synthesis and MMP-2 production. Receptor phosphorylation and signaling within the endosomal compartment have been documented for the insulin receptor kinase (15,25), and epidermal growth factor receptor activation and Shc recruitment within endosomes have also been observed (26,27). Reports have linked receptor internalization to the activation of the Shc/mitogen-activated protein kinase pathway (28,29).…”
Section: E-64 Inhibits Endosomal Proteolysis Of Igf-i-endosomalmentioning
confidence: 99%
“…It has been clearly shown that ligand degradation is a key event in receptor recycling (11,15) and signaling (27). Recently it was reported that anti-p185/HER2 antibody-mediated targeting of a cysteine proteinase inhibitor to a cathepsin Bcontaining intracellular compartment resulted in growth inhibition of two breast carcinoma cell lines including MCF-7 (32).…”
Section: E-64 Inhibits Endosomal Proteolysis Of Igf-i-endosomalmentioning
confidence: 99%